Pengaruh Keterlibatan Kerja, Karakteristik Pekerjaan, dan Dukungan Organisasi terhadap Komitmen Organisasi Pegawai pada Kantor Bupati Solok Selatan - Noverma Aisyi; Zusmawati Zusmawati (Lembaga Yasin AlSys, 2026)
Organizational commitment is an important aspect of human resource management, particularly in public sector organizations, because it is closely related to the quality of performance and organizational sustainability. This study aims to analyze the effect of job involvement, job characteristics, and organizational support on employees’ organizational commitment at the Office of the Regent of South Solok. This study employed a quantitative approach with a causal associative design, involving 99 respondents determined through total sampling. Data were collected using a questionnaire and analyzed with multiple linear regression using SPSS. The results showed that job involvement and job characteristics had a positive and significant effect on organizational commitment, whereas organizational support had no significant effect. These findings affirm that organizational commitment is more strongly influenced by employees’ attachment to their work and the quality of job design than by perceptions of organizational support. This study contributes to enriching the study of organizational behavior in the government sector and provides practical implications for government agencies in designing strategies to improve employee commitment through strengthening job involvement and improving job characteristics.